The heterogeneity of the RNA degradation exosome in Sulfolobus solfataricus - Witharana, Chamindri; Justus Liebig University Giessen (My University, 2013)
RNA processing and degradation are essential processes in the cell. The exosome of S. solfatarticus is able to degrade and polyadenylate RNA and is localized at the periphery of the cell. The in vitro reconstituted S. solfolobus exosome is built of a hexameric ring, containing Rrp41( the catalytically active subunit) and Rrp42 to which a trimeric cap of RNA binding proteins Rrp4 or Csl4 is bound. Rrp4 confers poly (A) specificity to the exosome. The archaeal DnaG protein which is homologues to the bacterial primase, and an Archaea specific exosomal subunit, directly binds to Csl4 protein in the exosome. The majority of Rrp41 and DnaG is detectable in the insoluble fraction and is localized at the cell periphery. In this study, it was found that the soluble and insoluble exosomes have different compositions. The soluble exosome contains less DnaG and less Csl4 than the insoluble exosome which co-sediments with ribosomal subunits in sucrose density gradients. However, after the RNase treatment the rRNA was completely degraded but the exosome sedimentation pattern was not changed. Furthermore potential interaction partners such as EF1α and Nop5 were found in the soluble exosome. The soluble and the insoluble exosomes were both active. However, different compositions of the exosome in the cell and thereby the localization could apparently be a common system in prokaryotes to separate biochemical processes in cells without compartmentalization. In this work Csl4 was co-immunoprecipitated with the exosome using anti-Rrp4 antibodies and vice versa. This finding clearly says that heteromeric RNA-binding caps are present in vivo. The presence of the heteromeric RNA binding cap probably ensures its interaction with different transcripts and probably different interaction partners. To understand the mechanism for poly (A) specificity of Rrp4, an exosome with an RNA-binding cap composed of truncated Rrp4 lacking the KH domain was reconstituted and analyzed. The deletion of the KH domain decreased the degradation activity, but the poly (A) specificity was retained. This finding says that the KH domain of the RNA binding Rrp4 protein is not responsible for the poly (A) specificity. It was further found that the proportion of soluble exosome increases in the stationary phase. Moreover the exosome amount increases under the cold stress conditions. The amount of exosome in pH high, pH low and heat stress was constant. These results strongly suggest that archeal exosome plays an important role under cold stress and in the stationary phase for the survival of the cells. Homologous cloning system was used to express recombinant His-tagged exosomal proteins in S. solfataricus. It was possible to clone the genes rrp4, csl4 and dnaG, as well as the dnaG parts encoding the N terminal and the C terminal portions of the protein, in to the pMJ0503 vector. However it was possible to transform and express only the full length DnaG-His6 in S. solfataricus M16. Overexpression was achieved in the stationary phase and the exosome containing DnaG-His6 and the native DnaG was isolated by Ni-NTA chromatography. For the first time, the native DnaG which was directly isolated from S. solfataricus was observed as a dimer with 2 lobes and a central pore using SPEM. The structure of the protein may help to solve many functions delusions.Parts of this work have been published:Witharana, C., V. Roppelt, G. Lochnit, G. Klug and E. Evguenieva-Hackenberg (2012). "Heterogeneous complexes of the RNA exosome in Sulfolobus solfataricus." Biochimie 94(7): 1578-87.
Untersuchungen zur Heterogenität des RNA degradierenden Exosoms in Sulfolobus solfataricus
Keywords: RNA; Degradation; Exosom; Archaea; Sulfolobus; RNA; degradation; exosome; Archaea; Sulfolobus; ddc:570